The 'personal work relationship' in Austria. Issue 3 (September 2019) - Brameshuber, Elisabeth
When assessing the personal work relationship in Austria, first the contractual relationship needs to be scrutinised. Following the differentiation between employees, semi-dependent workers (with the sub-category of employee-like working persons) and businesspersons, all, only some, or none, of the statutes and laws falling under the category of 'individual labour law' (e.g. Working Hours Act, Holidays Act etc) apply. Collective bargaining agreements, providing, amongst others, for minimum wages (N.B. there is no statutory minimum wage in Austria), can be concluded for employees only, though (with very few and specific exceptions for persons in the media sector). This paper analyses the legal situations of the different categories of working persons and critically assesses the non-application of most labour laws, including collective bargaining agreements, to employee-like working persons. It questions whether, from a teleological point of view, a different assessment would be necessary.